Why cannot modest teams win the league? The influence of the match schedule on the profile of the winnings teams - C. Lago (Asociación Española de Ciencias del Deporte, 2010)
The aim of this study is to analyze the influence of performance and chance on the results obtained by teams in football official competitions with different formats of competition. The research is based in data from 190 matches of the 2006/2007 Spanish Football League, 64 matches of the 2006 World Cup Germany and 125 matches of the 2005/20006 European Champions League. Performance is measured as the difference between shots attempted and shots received by a team in each game. Results from linear regression analysis show that in competitions with a league system, (Spanish Football League, first round of the 2006 World Cup Germany and first round of the 2005/20006 European Champions League) performance is a statistically significant variable for explaining the results obtained by teams. In competitions with a Knock-Out system (second round of the 2006 World Cup Germany and second round of the 2005/20006 European Champions League) there is not statistically significant differences in the performance obtained by winners and losers. I find that chance is a relevant variable for explaining the results of teams in competitions with a Knock-Out system. Key words:Schedukle of competition, peformance, chance, football